Food and food‐related waste management strategies in hospital food services: A systematic review. Issue 2 (27th September 2022) - Cook, Nathan; Goodwin, Denise; Porter, Judi; Collins, Jorja
Abstract: Aim: This review explored peer‐reviewed and grey literature to describe the types and characteristics of food or food‐related waste management strategies used in hospital food service settings; their financial, environmental and staffing outcomes; and the barriers and enablers associated with their implementation. Methods: Six electronic databases, 17 Google Advanced searches, and 19 targeted websites were searched for peer‐reviewed and grey literature. Literature reporting the financial, environmental, or staffing outcomes of food or food‐related waste management strategies that reused, recovered energy from, or recycled waste instead of sending it to landfill were eligible. Document screening and review were completed in duplicate, and included peer‐reviewed literature were assessed for quality using the Mixed Methods Appraisal Tool. Data were synthesised narratively. Results: Four peer‐reviewed and 81 grey literature records reported 85 strategies. When grouped from most to least favourable according to the food recovery hierarchy they managed waste by: donating surplus food ( n  = 21); feeding animals ( n  = 2); industrial use ( n  = 11); composting ( n  = 34) and other ( n  = 17). These approaches had the capacity to reduce waste hauling fees ( n  = 14), reduce staff handling of waste ( n  = 3), and decrease the amount of waste sent to landfill ( n  = 85). Barriers included contamination of waste streams, while enablers included leadership and time‐neutral changes. Conclusion: This review summarises the waste management strategies used by hospitals worldwide that divert food and food‐related waste from landfill, their outcomes, and position in the food recovery hierarchy to enable hospital food services to implement appropriate practice and policy changes to decrease their environmental footprint.